Estimating Social Preferences Using Stated Satisfaction: Novel Support for Inequity Aversion - Lina Diaz; Daniel Houser; John Ifcher; Homa Zarghamee (Institute of Labor Economics (IZA), 2021)
In this paper, we use stated satisfaction to estimate social preferences: subjects report their satisfaction with payment-profiles that hold their own payment constant while varying another subject's payment. This approach yields significant support for the inequity aversion model of Fehr and Schmidt (1999). This model is among the most renowned in behavioral economics, positing a generalized aversion to inequality that is stronger when one's own payoff is lower–rather than higher–than others'; i.e., "envy" is stronger than "guilt." While aggregate-level estimates based on revealed preferences in laboratory games have supported the model, the assumption that guilt is stronger than envy is often violated at the individual level. This paradox may be due to limitations of the revealed-preference approach. An advantage of avoiding games is that eliciting stated satisfaction is relatively easy to implement and is less prone to being confounded with motives like reciprocity; also the absence of tradeoffs between own and others' payoffs is cognitively less demanding for subjects. Our unstructured approach does not limit the expression of social preferences to inequity aversion, yet our methodology yields significant support for it. At the individual level, 86% of subjects exhibit at least as strong envy as guilt, and 76% (65%) of subjects weakly (strongly) adhere to the model. Our individual-level estimates are robust to changing the value of one's own constant payment and to changing the range of the other subject's payments. Methodologically, eliciting satisfaction can be an easy-to-implement complement to choice-based preference-measures in contexts other than social preferences that are of interest to economists.
Keywords: C91; D31; D63; I31; 330; inequity aversion; social preferences; stated satisfaction; laboratory experiment